Reconstruction of Vygotsky's Sociocultural Theory of Thinking in Learning Arabic Language at Elementary School Level - Roihanah Zakiyah; Resy Mulyani (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2024)
Learning Arabic is one of the important subjects at the elementary level. Therefore, greater attention is needed in the goals, implementation, and evaluation of learning. In learning Arabic, interaction with the environment and cognitive roles are necessary so that students can comprehensively learn the language in terms of practice and theory. Through this interaction, students' cognitive abilities will develop. As mentioned in Vygotsky's theory, students' cognitive abilities develop as they interact with their environment.